A kisajátítás helye új magánjogi kódexünkben - Andorkó, Imre (Debreceni Jogi Műhely, 2014)
The expropriation is a neglected legal institution in the Hungarian law, especially in the civil law. Although the expropriation usually appears in the civil law codes of the European states, it is ambiguous of the aspect of the civil law. However, it cannot be ignored that the civil law aspects of the expropriation are very important.In the civil law literature the expropriation is discussed either as the original way of acquisition of property or as the limit of the public property relations.My lecture is about the theoretical problems of the expropriation in the system of civil law. This article will provide an overview of doctrinal opinions about expropriation law in the delayed codification and in the new Hungarian civil law codex.